The Role of Somatostatin Receptor Scintigraphy on the Diagnosis of Desmoid Tumors. (31st May 2012) - Friesenbichler, Joerg; Molcan, Anja; Aigner, Reingard; Sadoghi, Patrick; Liegl-Atzwanger, Bernadette; Maurer-Ertl, Werner; Weger, Christian; Leithner, Andreas
Abstract : Background . Magnetic resonance imaging is considered as imaging modality of choice in diagnosis of desmoid tumors, though even this technique can lack the ability to distinguish aggressive fibromatosis from other benign or malignant soft tissue tumors. The aim of this study was to investigate if desmoid tumors would show an adequate tracer uptake in somatostatin receptor scintigraphy and moreover to correlate these results with immunohistochemical staining. Patients and Methods . Thirteen patients with desmoid tumors were examined with somatostatin receptor scintigraphy. Additionally, seven of these patients have been tested for the immunohistochemical expression of somatostatin receptor subtype 2A. The results of somatostatin receptor scintigraphy and the results of immunohistochemical staining (somatostatin receptor subtype 2A) were evaluated and correlated. Results . Somatostatin receptor scintigraphy revealed that eight of 13 affected patients (62%) showed an enhanced tracer uptake. On the other hand, the correlation between the results of somatostatin receptor scintigraphy and immunohistochemical investigations was poor (two out of seven cases). Conclusion . The current study demonstrated that desmoid tumors frequently express somatostatin receptor subtype 2, while immunohistochemical investigations did not correlate with these findings. This may likely be due to lack of standardization of this technique and also due to heterogeneous receptor distribution within the tumors.